2000
DOI: 10.1074/jbc.c000533200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of the Caspase-promoting Activity of Smac/DIABLO and Its Role in the Death Receptor Pathway

Abstract: Smac/DIABLO is a mitochondrial protein that is released along with cytochrome c during apoptosis and promotes cytochrome c-dependent caspase activation by neutralizing inhibitor of apoptosis proteins (IAPs). We provide evidence that Smac/DIABLO functions at the levels of both the Apaf-1-caspase-9 apoptosome and effector caspases. The N terminus of Smac/DIABLO is absolutely required for its ability to interact with the baculovirus IAP repeat (BIR3) of XIAP and to promote cytochrome c-dependent caspase activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
207
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(221 citation statements)
references
References 33 publications
12
207
2
Order By: Relevance
“…129 Recently, an IAP-neutralizing and therefore apoptosis-promoting mitochondrial protein, termed Leukemia Smac/Diablo, has been identified that obviously plays a critical role in antagonizing the caspase-inhibitory effect of IAPs. 130,131 The role of Smac in tumor biology is as yet unclear but inactivation of this novel player could also result in a resistant phenotype. Thus, death receptor-targeted therapeutic approaches may encounter similar problems as conventional chemo-or radiotherapy.…”
Section: Death Ligands In Cancer Therapymentioning
confidence: 99%
“…129 Recently, an IAP-neutralizing and therefore apoptosis-promoting mitochondrial protein, termed Leukemia Smac/Diablo, has been identified that obviously plays a critical role in antagonizing the caspase-inhibitory effect of IAPs. 130,131 The role of Smac in tumor biology is as yet unclear but inactivation of this novel player could also result in a resistant phenotype. Thus, death receptor-targeted therapeutic approaches may encounter similar problems as conventional chemo-or radiotherapy.…”
Section: Death Ligands In Cancer Therapymentioning
confidence: 99%
“…Active caspase-9 cleaves and activates the effector caspases-3, -6 and -7, which in turn, by cleaving their substrates, complete the apoptotic cell death. Along with cytochrome C the Smac/DIABLO protein is released into the cytoplasm and binds to IAPs, thereby inhibiting them, and consequently allowing the caspases to complete the apoptotic process (Srinivasula et al, 2000). Bcl-x L is an antiapoptotic protein, which similarly to Bcl-2 prevents the mitochondrial membrane disruption (reviewed by .…”
Section: Badmentioning
confidence: 99%
“…[5][6][7] The third BIR domain of XIAP has been the most well-studied BIR in terms of defining the consensus IBM sequence. [8][9][10][11] Examples of proteins that bind to BIRs in an IBM-dependent manner include the caspases, 11,12 the second mitochondrial activator of caspase (SMAC -also known as DIABLO) 13,14 and HtrA2 (also known as Omi), 15 and the Drosophila proteins Hid, Grim and Reaper -reviewed in Bangs et al 16 The most documented function of IAP-binding proteins is to compete with caspases, and thereby abrogate caspase regulation.…”
mentioning
confidence: 99%